2019
DOI: 10.3389/fendo.2019.00634
|View full text |Cite
|
Sign up to set email alerts
|

In Addition to Poor Glycemic Control, a High Level of Irisin in the Plasma Portends Early Cognitive Deficits Clinically in Chinese Patients With Type 2 Diabetes Mellitus

Abstract: Background and Objectives: Irisin plays an important role in the metabolism and homeostasis of energy balance, which is involved in cognitive impairment. This study aimed to investigate the role of irisin in mild cognitive impairment (MCI) among Chinese patients with type 2 diabetes mellitus (T2DM).Methods: We recruited 133 Chinese patients with T2DM, and divided them according to the Montreal Cognitive Assessment score. Demographic data were collected and the level of irisin in the plasma was determined. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Elevated concentrations of plasma irisin have been associated with impaired cognitive abilities, particularly in the executive function domain. Additionally, linear regression analysis demonstrated a correlation between irisin and glycated hemoglobin, and both were independent risk factors for MCI in diabetes ( 70 ).…”
Section: Fndc5/irisin In Cognitive Impairment and Dementia Caused By ...mentioning
confidence: 99%
“…Elevated concentrations of plasma irisin have been associated with impaired cognitive abilities, particularly in the executive function domain. Additionally, linear regression analysis demonstrated a correlation between irisin and glycated hemoglobin, and both were independent risk factors for MCI in diabetes ( 70 ).…”
Section: Fndc5/irisin In Cognitive Impairment and Dementia Caused By ...mentioning
confidence: 99%
“…Lin et al, evaluated 133 Chinese patients, aged 45–75 years, with T2DM, where 59 patients were diagnosed with mild cognitive impairment (MCI) and 74 patients were included as healthy-cognition controls [ 75 ]. The main findings of this study revealed that patients with T2DM who had MCI presented significant higher levels of irisin, HbA1c, and insulin.…”
Section: Exercise-linked Irisin: Consequences On Mental Health In mentioning
confidence: 99%
“…In a study conducted in patients diagnosed with T2DM and mild cognitive impairment, the level of irisin in plasma correlated with cognitive impairment (especially executive function) in T2DM patients. Based on these results, researchers claimed that high irisin levels in plasma cause clinical early cognitive deficits in patients with T2DM [89].…”
Section: Type 2 Diabetes Mellitus Depression and Irisinmentioning
confidence: 99%